2015
DOI: 10.17795/ijcp-4032
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Growth Inhibitory Capacity of Several Medicinal Plants From Iran on Tumor Cell Lines

Abstract: Background:Traditional herbal medicine is a valuable resource that provides new drugs for cancer treatment. Objectives:In this study we aim to screen and investigate the in vitro anti-tumor activities of ten species of plants commonly grown in Southern Iran. Materials and Methods:We used the MTT colorimetric assay to evaluate the cytotoxic activities of the methanol extracts of these plants on various tumor cell lines. The IC50 was calculated as a scale for this evaluation.Results:Satureja bachtiarica, Saturej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 28 publications
1
17
1
2
Order By: Relevance
“…In a study accomplished by Esmaeilbeig et al, it was reported that IC50 of Cichorium intybus extract on Jurkat cell line was 138µg/mL after 48 hours and they also stated that Chicorium intybus extract could decrease the cell viability in Hela (Cervical Epitheloid Carcinoma) and Fen (Bladder Carcinoma) cell lines after considered treatment (18).…”
Section: Discussionmentioning
confidence: 99%
“…In a study accomplished by Esmaeilbeig et al, it was reported that IC50 of Cichorium intybus extract on Jurkat cell line was 138µg/mL after 48 hours and they also stated that Chicorium intybus extract could decrease the cell viability in Hela (Cervical Epitheloid Carcinoma) and Fen (Bladder Carcinoma) cell lines after considered treatment (18).…”
Section: Discussionmentioning
confidence: 99%
“…The detected antioxidant activity encouraged the use of this plant for its antioxidant properties in food industries and in cosmetic and pharmaceutical preparations. The results evidenced strong cytotoxicity against HT-29 and HepG-2 cell lines and interesting apoptosis induction ability; the authors suggested further studies in this field [35]. Jassbi et al (2016) [32] tested the cytotoxic activity, against three human cancer cell lines (LS180, MCF-7, and MOLT-4), of dichloromethane and methanol extracts of Anthemis mirheydari, an endemic plant from Iran.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…At the same concentration, these extracts inhibited the K562 cell line with more than 50% of inhibition[36]. Further studies are needed to identify the main active compounds.Hamzeloo-Moghadam et al (2015)[35] tested the cytotoxic activity and the apoptosis induction activity of different fractions obtained by methanolic extract of Hypericum scabrum leaves. The plant was collected from Alborz province, Iran.…”
mentioning
confidence: 99%
“…5 Fruits and veggies are the primary source of antioxidants' vitamins, making these foods essential to human health. 6 Esmaeil beiget al 7 believes that safe, nontoxic origin of herbs and plants have valuable sources for novel anti-cancer drugs. According to Bauman,8 in fruits, there are important nutrient besides other vitamins, minerals, flavonoids and phytochemicals, which have been reported as a good contributing factor to the health.In addition, epidemiological studies, including experiments performed on animal models and investigations on humans have proven that consumption of a diet rich in vegetables and fruits is associated with a low risk of contracting some diseases, including cardiovascular diseases and cancers.…”
Section: Introductionmentioning
confidence: 99%